Tracheostomy Outcomes in Patients With COVID-19 at a New York City Hospital - Rahul K. Sharma MD; Maeher R. Grewal; Sallie M. Long MD; Brendon DiDonna PA-C; Joshua Sturm MD, PhD; Susannah E. Hills MD; Scott H. Troob MD (OTO Open, 2022)
Objective Tracheostomies have been performed in patients with prolonged intubation due to COVID-19. Understanding outcomes in different populations is crucial to tackle future epidemics. Study Design Prospective cohort study. Setting Tertiary academic medical center in New York City. Methods A prospectively collected database of patients with COVID-19 undergoing open tracheostomy between March 2020 and April 2020 was reviewed. Primary endpoints were weaning from the ventilator and from sedation and time to decannulation. Results Sixty-six patients underwent tracheostomy. There were 42 males (64%) with an average age of 62 years (range, 23-91). Patients were intubated for a median time of 26 days prior to tracheostomy (interquartile range [IQR], 23-30). The median time to weaning from ventilatory support after tracheostomy was 18 days (IQR, 10-29). Of those sedated at the time of tracheostomy, the median time to discontinuation of sedation was 5 days (IQR, 3-9). Of patients who survived, 39 (69%) were decannulated. Of those decannulated before discharge (n = 39), the median time to decannulation was 36 days (IQR, 27-49) following tracheostomy. The median time from ventilator liberation to decannulation was 14 days (IQR, 8-22). Thirteen patients (20.0%) had minor bleeding requiring packing. Two patients (3%) had bleeding requiring neck exploration. The all-cause mortality rate was 10.6%. No patients died of procedural causes, and no surgeons acquired COVID-19. Conclusion Open tracheostomies were successfully and safely performed at our institution in the peak of the COVID-19 pandemic. The majority of patients were successfully weaned from the ventilator and sedation. Approximately 60% of patients were decannulated prior to hospital discharge.